In vitro Metabolomic Approaches to Investigating the Potential Biological Effects of Phenolic Compounds: An Update - Úrsula Catalán; Laura Barrubés; Rosa Maria Valls; Rosa Solà; Laura Rubió (Genomics, Proteomics & Bioinformatics, 2017)
Dietary phenolic compounds (PCs) have been receiving interest for their presumed roles in disease prevention. However, there is a lack of studies on the underlying molecular mechanisms. In this regard, in vitro metabolomic approaches are suitable for the investigation of the molecular changes in response to PC exposure. Up to date, the biological effects of PCs have only been examined for PCs from rosemary (Rosmarinus officinalis), olive oil, and resveratrol using cell-based metabolomic approach, although transcriptomic and/or proteomic studies have also been conducted in the same in vitro cell experiment in some cases. Our integral analysis of the reviewed studies suggest that PCs may be involved not only in basic cellular processes or macro- and micro-nutrient metabolism, but also in specific metabolic pathways that have been thoroughly investigated. These modulated pathways could have a clinical impact on neurodegenerative diseases, type 2 diabetes, cancer, and cardiovascular diseases. In conclusion, the in vitro metabolomic approaches provide additional information of the molecular mechanisms involved in disease risk reduction of dietary PCs. In order to elucidate the mechanisms of action of PCs, more metabolomic cell-based studies are needed and testing the physiological conjugated forms of PCs in these cell systems could be of special interest.